Analisis Faktor yang Mempengaruhi Minat Belajar Siswa Kelas XI Akuntansi SMK Negeri 1 Makassar - Yusriatia, Yusriatia; Hasyim, Sitti Hajerah; Azis, Fajriani (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2024)
This study aims to analyze the factors influencing students' interest in learning in Class XI of the Accounting Expertise Program at SMK Negeri 1 Makassar. The study population consists of 144 students, with a sample of 60 students selected using the Proportionate Stratified Random Sampling technique. Data were collected through questionnaires and analyzed using factor analysis with SPSS version 25.0.The research results indicate that the first factor, with an eigenvalue of 4.878, consists of the variables health and fitness conditions, intelligence, student interest, school, and study time. The second factor, with a value of 1.701, includes attitude, family, subject matter, and home conditions. The third factor, with a value of 1.569, comprises student talents, classmates, building, and location, while the fourth factor, with a value of 1.267, includes motivation and society.The most important factor influencing students' interest in learning is student interest, with a value of 0.880. This shows that students' special attention to subjects serves as a strong incentive for active involvement in the learning process.